Distance Learning: The Case of Political Science - Schmidt, Steffen; Shelley, Mark C.; Van Wart, Monty; Clayton, Jane; Schreck, Erin (Education Policy Analysis Archives, 2000)
This article reports the results from a national survey directed to the department chairs of political science to assess the current and future state of distance learning in that discipline. The insights of this research are relevant to all social science fields and offer important insights to other academic disciplines as well. Key findings of the study include the low utilization of distance learning courses, a low degree of importance currently attributed to distance learning and modest expectations of future growth, ambivalent acceptance of a future role for distance learning, the common use of Internet-related technologies, low levels of faculty knowledge and interest about distance learning, limited institutional support, and serious doubts about the appropriateness and quality of instruction at a distance. We propose a model of the size and scope of distance learning as a function of three factors: the capacity of distance learning technologies, market demand, and faculty and university interest in distance learning. The article concludes with suggestions of critical areas for future research in this dynamic, fluid post-secondary environment.